Serum Vitamin D Profiles of Children with Asthma in Southwest Saudi: A Comparative Cross-Sectional Study - Asseri AA (International Journal of General Medicine)
Ali Alsuheel Asseri Department of Child Health, King Khalid University, Abha, 62529, Saudi ArabiaCorrespondence: Ali Alsuheel Asseri, Department of Child Health, King Khalid University, Abha, 62529, Saudi Arabia, Tel +966500186013, Fax +9662418139, Email alsoheel11@kku.edu.saBackground: Evidence suggests a strong association between vitamin D status and asthma, with individuals exhibiting vitamin D deficiency demonstrating increased prevalence and severity of asthma symptoms. This study aimed to determine the prevalence of vitamin D deficiency among asthmatic children, assess the association between vitamin D status and asthma severity/control, and identify potential predictors of vitamin D deficiency in this population.Patients and Methods: This comparative cross-sectional, hospital-based study was conducted at Abha Maternity and Children’s Hospital, a tertiary care and teaching institution in southwestern Saudi Arabia, between January 2023 and May 2024.Results: A total of 331 asthmatic children and 101 non-asthmatic children were analyzed. Children with asthma had significantly lower serum vitamin D levels than those without asthma (21.5 ± 8.8 ng/mL vs 33.3 ± 13.2 ng/mL, p < 0.001). Significantly higher proportions of asthmatic children exhibited vitamin D deficiency (51.1%) and insufficiency (34.7%) compared to non-asthmatic children (19.8% and 29.7%, respectively). Serum vitamin D levels among asthmatic children showed significant negative correlations with age (r = − 0.332, p < 0.001), weight (r = − 0.292, p < 0.001), height (r = − 0.298, p < 0.001), and BMI (r = − 0.274, p < 0.001). These findings were further supported by univariate linear regression analysis. Multivariable analysis additionally confirmed age (β = − 0.66, p < 0.001) and BMI (β = − 0.25, p = 0.05) as independent predictors of vitamin D status, with older age and higher BMI associated with lower vitamin D levels. For each additional year of age, serum vitamin D decreased by an average of 0.66 ng/mL (p < 0.001) and a one-unit increase in BMI was associated with a decrease of 0.25 ng/mL in serum vitamin D (p = 0.05).Conclusion: This study found a strikingly high prevalence of vitamin D deficiency among asthmatic children in southwestern Saudi Arabia, significantly exceeding rates in controls. These findings underscore the need for widespread vitamin D screening and supplementation in this population, particularly among older, overweight asthmatic children.Keywords: children, asthma, vitamin D deficiency, Saudi Arabia, obesity